Management of the Internal Quality Assurance System (SPMI) for Higher Education - Sugesti, Tutik (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
The purpose of this research is to discuss or examine the management of the internal quality assurance system (SPMI) for higher education. The method used is literature study which is objective, systematic, analytical and descriptive. The conclusion of this research is: The internal quality assurance system (SPMI) is an effort to improve the quality of higher education. With the quality of Indonesian higher education still lagging behind other countries, this is a very big problem for Indonesian higher education today. The problem of the quality of higher education which is still low is the reason why the government provides a policy by introducing an internal quality assurance system (SPMI) in higher education. The internal quality assurance system (SPMI) is managed independently by the university concerned. Then, higher education quality management is carried out on an ongoing basis.